(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The present article investigates English and Uzbek phraseological units which reflect the content of the concept “holiday”. The author gives examples of such units and reveals their historical, ethnic-cultural and national-specific potential.